Assessment of Geosite and Geotourism Potential of Baskil District (Elazığ) Using Preliminary Geosite Assessment Model (GAM) - Goktas, Yaren; Aytac, Ahmet Serdar; Sengun, Mustafa Taner; Kocaoglu, Muhammed (Springer Heidelberg, 2025)
Geosites bearing the traces of geological and geomorphological processes play an important role in sustainable geotourism development. This study aims to analyze the geotourism potential of eight potential geosites located in Baskil district of Elaz & imath;& gbreve; province through the Preliminary Geosite Assessment Model (GAM). The geosites examined include Baskil Magmatites, Keban and K & ouml;m & uuml;rhan Gorges, Karaleylek and Sakl & imath;kap & imath; Canyons, Tepesidelik Cave, G & uuml;m & uuml;& scedil;& ccedil;ay Canyon and Kad & imath;k & ouml;y Alluvial Fan. In the study, these areas were evaluated in terms of scientific, aesthetic, functional and tourism-related criteria. The findings reveal that the geosites have high scientific and geological importance, but touristic infrastructure and promotional activities are inadequate. Sakl & imath;kap & imath; and Karaleylek Canyons received the highest scores in terms of main values, while functional and touristic values were generally low. The results show that Baskil district has geotourism and geopark potential at national and international levels. However, to unlock this potential, it is of great importance to implement strategic planning that prioritizes protection, accessibility and the participation of local people.
Keywords: Geosite assessment; Geotourism; Geoheritage; Geopark; Preliminary geosite assessment model; Baskil (Elaz & imath;& gbreve;)